A SOCIOLINGUISTICS STUDY OF ENGLISH - INDONESIAN CODE MIXING USED IN PULSA MAGAZINE - SYAIFULLAH , ARIEF (2010)
This research is aimed at describing the kinds of code mixing used in pulsa magazine, and the factors causing the uses of code mixing. The data are 39 code mixing that are taken from pulsa magazine edition 160th VII/2009 and 168th VII/2009.In collecting the data, the writer uses documentation method by note taking the occurrence of English code mixing, which can be found in the pulsa magazine. The first step is classifying the data of code mixing based on linguistics, types, and factors. Then analyze the code mixing using sociolinguistics theory. The results of this research show that: In form of code mixing there are found word and phrase. The word consists of simple word and complex word. In simple word there found 14 datum or about 40%. First, in complex word there three kinds; compounding word, affixation and hybrid. There found 12 datum or about 34,3% for compounding word, in affixation there are found 8 datum or about 22,8%, and in hybrid there are found 2 datum or about 5,7%. The last form of code mixing is phrase which is consists of 3 datum or about 8,6%. The second The motives are needs to fill motive, prestige filling motive. In need feeling motives there are 31 data used in Pulsa Magazine. So the percentage from the whole need feeling motive are 88,6% because in Pulsa Magazine the journalist always uses the name or the term related to phone cell. In prestige feeling motives there are only 4 data used in Pulsa Magazine. So the percentage from the whole prestige feeling motive are 11,4% because there is only a little person uses prestige in cellular world needed to control and attract the costumers. The other reason is respect, there are only 4 data found in Pulsa Magazine and the data also exist in prestige feeling motive. So the percentage from the whole respect reason are 11,4% because prestige is also one way to gat respect.